2019
DOI: 10.5830/cvja-2019-026
|View full text |Cite
|
Sign up to set email alerts
|

Plasma phospholipid fatty acid patterns are associated with adiposity and the metabolic syndrome in black South Africans: a cross-sectional study

Abstract: Background: Diets rich in n-6 polyunsaturated fatty acids (PUFAs) and saturated fatty acids (SFA) have been associated with increased risk of obesity and the metabolic syndrome (MetS), but the evidence is inconsistent, whereas diets high in n-3 long-chain (LC)-PUFAs are associated with lower risk. There is limited information about the association of plasma phospholipid fatty acids (FAs) with obesity and the MetS among black South Africans. Objective: To investigate the association of dietary FAs and plasma ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 49 publications
(80 reference statements)
3
5
0
Order By: Relevance
“…In contrast, higher total SFA in RBC-TPL, but not in SAT depots, was associated with lower S I . These findings are similar to a previous study in black SA individuals showing a positive association between SFAs in plasma phospholipids and measures of adiposity and metabolic syndrome [50]. High intake of dietary SFA may significantly increase IR via alterations of desaturases activity (mainly D5D and D9D) in cell membrane phospholipids and inhibition of insulin-stimulated Akt activation followed by the reduction in glucose uptake [16,56].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In contrast, higher total SFA in RBC-TPL, but not in SAT depots, was associated with lower S I . These findings are similar to a previous study in black SA individuals showing a positive association between SFAs in plasma phospholipids and measures of adiposity and metabolic syndrome [50]. High intake of dietary SFA may significantly increase IR via alterations of desaturases activity (mainly D5D and D9D) in cell membrane phospholipids and inhibition of insulin-stimulated Akt activation followed by the reduction in glucose uptake [16,56].…”
Section: Discussionsupporting
confidence: 90%
“…SCD1-16 is involved in the endogenous synthesis of MUFA from SFA and is mainly active in AT, where it plays a central role for de novo synthesis and storage of excess energy as triglycerides [17]. Accordingly, oleic acid (18:1n-9) has been reported as the major species in adipose triglycerides [12,44,[48][49][50]. Similarly, oleic acid was the most abundant FA in SAT depots (32.5%) in our study.…”
Section: Discussionsupporting
confidence: 60%
“…We reported dietary and fat intake profiles across urbanisation categories in line with previously reported baseline dietary intake for the complete cohort ( n 1950) [5] implying generalizability of our results to the population of black South Africans. Herein reported plasma fatty acid profiles are comparable to recent report within larger sample ( n 711) [18] of the same cohort of black South Africans participating PURE, outweighing potential concern on the limited sample size of 300 subjects. Of note, 10-year attrition rate might have blurred some of the associations.…”
Section: Discussionsupporting
confidence: 84%
“…In middle-aged and elderly Chinese community dwellers, serum patterns presenting with high DHA levels were inversely associated with BP [12] and hypertension status [17]. Recent data from the PURE study showed association between plasma phospholipid fatty acid patterns and obesity and metabolic syndrome in black South African adults [18], however the link with vascular function has not yet been examined in the population.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, glucomannan-enriched Aronia juice with around 600 mg/100g polyphenols tended to reduce body weight and significantly reduced BMI in women with abdominal obesity after 4 weeks [15], which might be due to the glucomannan effects [48]. Furthermore, a number of epidemiological studies demonstrated a link between fatty acids in plasma phospholipids and parameters of obesity and metabolic syndrome [4,49]. Cross sectional-studies also reported the inverse association between EPA levels in erythrocyte membranes and BMI [50] and subjects who are obese had lower EPA levels in plasma phospholipids in comparison with their lean counterparts [51].…”
Section: Discussionmentioning
confidence: 97%